Perceived quality of care among people with type 2 diabetes mellitus in the north east region of peninsular Malaysia - Noorfariza Nordin; Suhaily Mohd Hairon; Najib Majdi Yaacob; Anees Abdul Hamid; Seoparjoo Azmel Mohd Isa; Norzaihan Hassan (BMC, 2021)
Abstract Background People with type 2 diabetes mellitus (T2DM) are best managed by a chronic care model that is associated with enhanced quality of care and improved patient outcome. Assessing patients' perceived quality of care is crucial in improving the healthcare delivery system. Hence, this study determined the perceived quality of care among people with T2DM and explored its associations with (i) sociodemographic and clinical characteristics and (ii) types of healthcare clinics to guide future planning. Methods A cross-sectional study involving 20 primary healthcare clinics in the North East Region of Peninsular Malaysia and people with T2DM as the sampling unit was conducted from February to May 2019. The pro forma checklist, interview-guided Skala Kepuasan Interaksi Perubatan-11, and Patient Assessment of Chronic Illness Care (Malay version; PACIC-M) questionnaire were used for data collection. Univariate analysis and linear regression were used to determine the status of perceived quality of care and the factors associated with the perceived quality of care, respectively. Results Overall, data from 772 participants were analyzed. The majority was from the Malay ethnic group (95.6%) with a mean (standard deviation [SD]) glycated hemoglobin A1c (HbA1c) level of 8.91% (2.30). The median (interquartile range [IQR]) of the number of medical officers available at each clinic was 6 (7), with Family Doctor Concept (FDC) clinics having a higher number of medical officers than non-FDC clinics (p = 0.001). The overall mean (SD) PACIC-M score was 2.65 (0.54) with no significant difference between scores of patients treated in the two clinic types (p = 0.806). Higher perceived quality of care was associated with lower number of medical officers (adjusted regression coefficient [Adj.β], − 0.021; p-value [p], 0.001), and greater doctor-patient interaction in all domains: distress relief (Adj.β, 0.033; p, < 0.001), rapport (Adj.β, 0.056; p, < 0.001), and interaction outcome (Adj.β, 0.022; p, 0.003). Conclusion Although there was no significant difference found between clinic type, this study reflects that patients are comfortable when managed by the same doctor, which may support a better doctor-patient interaction. A larger specialized primary care workforce could improve diabetes care in Malaysia.